PERMINTAAN BAWANG MERAH DI KOTA SURAKARTA: SEBUAH ANALISA - suswadi, suswadi; Prasetyo, Agung; Irawan, Norbertus Citra (Universitas Islam Kadiri, 2023)
Shallots (Allium ascalonicum L.) is one of the primary vegetable commodities with many benefits. Shallots (Allium ascalonicum L.) contain carbohydrates, sugars, fatty acids, proteins, and other minerals needed by the human body. So that at certain times, shallots experience price fluctuations in the form of price increases when demand is higher than supply, and shallot prices decline when the supply is higher than demand. This study aims to analyze the factors that influence the demand for shallots to determine the elasticity of demand for shallots in the city of Surakarta with the factors that influence it. The primary method used is descriptive-analytical. The method of determining the location used is a purposive method defined intentionally, namely in Surakarta. The data used is secondary data using time series data from 2000-2019. The multiple linear regression analysis results show that the price of garlic, the price of red chili, the population, and income per capita individually significantly affect the demand for shallots in Surakarta. Price elasticity in this study could not be determined. Cross elasticity shows that red goods are substituted with garlic and red chili in Surakarta City. The income elasticity value is positive or more than zero and less than one, indicating that shallots are included in the normal goods and necessities category.